WPSI-9 Dietary DL-methionine supplementation alleviates early liver injury of intra-uterine growth retarded suckling piglets. (7th December 2018) - Htoo, J; Hao, Z; Y, L; Y, C; Z, Y; W, S; Tao, Z; Yan, D; Zhang, L; Tian, W
Abstract: The present study investigated the effects of dietary DL-methionine (DL-Met) supplementation on growth performance and hepatic injury and redox status of suckling piglets with intra-uterine growth retardation (IUGR). Six normal birth weight (NBW) and 12 IUGR piglets were selected at birth. They were received basal milk diet supplemented with 0.16% L-alanine (NBW-CON), 0.16% L-alanine (IUGR-CON) or 0.10% DL-Met (IUGR-MET) from 7 to 21 days of age, respectively (n = 6). Piglets in the IUGR-CON group exhibited a compromised growth performance, higher levels of liver injury markers in plasma and increased oxidative damage in liver, when compared with the NBW-CON group (P < 0.05). Dietary supplementation of DL-Met attenuated liver injury induced by IUGR with evidence of the decreased alanine transferase activity (P = 0.018) and numerically reduced total bilirubin content (P = 0.059) in plasma. Additionally, DL-Met administration effectively decreased the content of protein carbonyl (P = 0.021) and 4-hydroxynonenal (P = 0.027) in the liver of IUGR piglets, mostly owing to the stimulation of DL-Met supplementation on hepatic insulin-like growth factor 1 content (P = 0.017) and the expression of methionine sulfoxide reductase A at both mRNA (P = 0.021) and protein (P = 0.025) levels. This study demonstrates that dietary DL-Met supplementation may have some potential protective effects in alleviating the early liver injury of IUGR suckling piglets.